A Putative Role of Teneurin-2 and Its Related Proteins in Astrocytes - Tessarin, Gestter W. L.; Michalec, Ola M.; Torres-da-Silva, Kelly R.; Da Silva, André V.; Cruz-Rizzolo, Roelf J.; Gonçalves, Alaide; Gasparini, Daniele C.; Horta-Júnior, José A. C.; Ervolino, Edilson; Bittencourt, Jackson C.; Lovejoy, David A.; Casatti, Cláudio A. (Frontiers in Neuroscience, 2019)
Teneurins are type II transmembrane proteins comprised of four phylogenetically conserved homologues (Ten-1-4) that are highly expressed during neurogenesis. An additional bioactive peptide named teneurin C-terminal-associated peptide (TCAP-1-4) is present in the carboxyl terminal of teneurins. The possible correlation between the teneurin/TCAP system and brain injuries has not been explored yet. Thus, this study mainly focused on whether these proteins are regulated in the cerebral cortex after mechanical brain injury. For this purpose, adult rats were submitted to cerebral cortex injury by needle-insertion lesion, sacrificed at different time points, followed by analysis of the lesion area by immunohistochemistry and conventional RT-PCR techniques. Immortalized cerebellar astrocytes were also evaluated for Ten/TCAP expressions and intracellular calcium signaling by fluorescence microscopy after TCAP-1 treatment. Control group animals showed only discrete Ten-2-like immunoreactive pyramidal neurons in the cerebral cortex. In contrast, this immunoreactivity was significantly up-regulated in reactive astrocytes in all brain-injured groups (p<0.0001) when compared to control. Interestingly, reactive astrocytes showed intense immunoreactivity to LPHN-1, an endogenous receptor for Ten-2 splice variant named Lasso. Semi-quantitative analysis of Ten-2 and TCAP-2 expressions revealed significant increases at 48 hours, 3 days and 5 days (p<0.0001) after brain injury when compared with the remaining groups. Immortalized astrocytes expressed additional Ten/TCAP homologues and exhibited significant increases in intracellular calcium concentrations after TCAP-1 treatment. In conclusion, this study is the first to demonstrate that Ten-2/TCAP-2 and LPHN-1 are upregulated in reactive astrocytes after mechanical brain injury. Immortalized cerebellar astrocytes expressed Ten/TCAP homologues and TCAP-1 treatment stimulated intracellular calcium signaling. These findings disclose a new functional role of the Ten/TCAP system in astrocytes during tissue repair of the CNS.